2015
DOI: 10.1039/c4cp05316h
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopy as a probe for lithium polysulfide radicals

Abstract: The discharge mechanism in lithium sulfur batteries is still unknown and has been purported to involve significant concentrations of polysulfide radicals. Methods capable of quantifying these species in solution are therefore of paramount importance to revealing electrochemical pathways. Here we utilize DFT based X-ray Absorption Spectroscopy (XAS) simulations at the sulfur K-edge to obtain the spectra of polysulfide molecules in neutral, radical (-1) and dianionic (-2) charge states. Our calculations indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
52
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 54 publications
7
52
1
Order By: Relevance
“…As shown in Figure 2c, eq 5 predicts the free energy of sulfur encapsulated in various sized nanopores, as well as at the graphene interface, to within 3% of the values calculated from MD simulations over the entire liquid temperature range ( Figure S6). As with our previous efforts, 34,35 we aim to uncover electronic structure changes upon sulfur impregnation into microporous carbon that can be exploited to both resolve the underlying physical morphologies and reveal molecular scale details of function. A previous study demonstrated that surface molecules at metal interfaces have unique electronic structure, manifested as modulations of their X-ray absorption spectra (XAS).…”
mentioning
confidence: 99%
“…As shown in Figure 2c, eq 5 predicts the free energy of sulfur encapsulated in various sized nanopores, as well as at the graphene interface, to within 3% of the values calculated from MD simulations over the entire liquid temperature range ( Figure S6). As with our previous efforts, 34,35 we aim to uncover electronic structure changes upon sulfur impregnation into microporous carbon that can be exploited to both resolve the underlying physical morphologies and reveal molecular scale details of function. A previous study demonstrated that surface molecules at metal interfaces have unique electronic structure, manifested as modulations of their X-ray absorption spectra (XAS).…”
mentioning
confidence: 99%
“…[ 22 ] In a previous work, we demonstrated that the XAS of dissolved lithium polysulfi de dianion species can be obtained via condensed-phase fi rst-principles molecular dynamics and DFT spectral simulations. [ 21 ] More recently, we extended our approach to the various polysulfi de radicals in vacuum [ 26 ] and have predicted that XAS can detect the trisulfur radical against a background of longer chain polysulfi de dianions at a ≈20% molar concentration (or ≈4% by spectral composition) at 0.1-0.2 eV spectral resolution. Our condensed phase DFT approach has been proven accurate when compared to measured spectra of known sulfur containing compounds and is extremely insightful for interpreting spectra based on the atomic and electronic properties of the molecule of interest.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21,22,26 ] Vijayakumar et al calculated the XAS of the various polysulfi des, including the trisulfur radical, in vacuum and in a solvation shell of six DMSO molecules using time-dependent DFT calculations, and used these spectra to fi ngerprint experimental measurements. [ 22 ] In a previous work, we demonstrated that the XAS of dissolved lithium polysulfi de dianion species can be obtained via condensed-phase fi rst-principles molecular dynamics and DFT spectral simulations.…”
Section: Introductionmentioning
confidence: 99%
“…26,31 In this work, in situ X-ray absorption spectroscopy at the sulfur K-edge is used to examine an Li-S cell cathode during discharge. The low energy of sulfur K-edge X-rays, and the presence of sulfur in the cathode (which absorbs sulfur K-edge X-rays) limited the penetration of X-rays into the cathode.…”
mentioning
confidence: 99%
“…[28][29][30] However, we have recently shown that the X-ray absorption spectra for lithium polysulfide molecules can be calculated from first principles, thus enabling unambiguous interpretation of experimentally obtained X-ray spectra. 26,31 In this work, in situ X-ray absorption spectroscopy at the sulfur K-edge is used to examine an Li-S cell cathode during discharge. The low energy of sulfur K-edge X-rays, and the presence of sulfur in the cathode (which absorbs sulfur K-edge X-rays) limited the penetration of X-rays into the cathode.…”
mentioning
confidence: 99%